The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5535/arm.2013.37.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Changes of Spine in Helicopter Pilots

Abstract: ObjectiveTo determine the relationship between whole body vibration (WBV) induced helicopter flights and degenerative changes of the cervical and lumbar spine.MethodsWe examined 186 helicopter pilots who were exposed to WBV and 94 military clerical workers at a military hospital. Questionnaires and interviews were completed for 164 of the 186 pilots (response rate, 88.2%) and 88 of the 94 clerical workers (response rate, 93.6%). Radiographic examinations of the cervical and the lumbar spines were performed aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…Performing high-G manoeuvres [41], pilot ejection [42], and helicopter vibration [43] present risk factors for injury to the neck. Potentially, the resulting high-compressive forces on the spine could result in end plate fractures, then leading to adjacent IVD degeneration [44].…”
Section: Cumulative Injury To the Ivd Prior To Spaceflightmentioning
confidence: 99%
“…Performing high-G manoeuvres [41], pilot ejection [42], and helicopter vibration [43] present risk factors for injury to the neck. Potentially, the resulting high-compressive forces on the spine could result in end plate fractures, then leading to adjacent IVD degeneration [44].…”
Section: Cumulative Injury To the Ivd Prior To Spaceflightmentioning
confidence: 99%
“…Accumulated flight hours in helicopter pilots have been associated with increased degenerative changes of the cervical spine. 2 Fixed wing pilots are also affected by the weighted performance gear and flight helmets but are exposed to positive gravitational (+Gx, Gy, Gz) forces that may accelerate disc degeneration. 1,2,4,8,13 A 1996 study found that 7.4% of US Army aviators were removed from flight status due to cervical and lumbar herniated discs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Fixed wing pilots are also affected by the weighted performance gear and flight helmets but are exposed to positive gravitational (+Gx, Gy, Gz) forces that may accelerate disc degeneration. 1,2,4,8,13 A 1996 study found that 7.4% of US Army aviators were removed from flight status due to cervical and lumbar herniated discs. 6 While the symptoms of cervical spondylosis may not severely limit the average individual's career, they are significant for military pilots.…”
Section: Discussionmentioning
confidence: 99%
“…Elles entraînent une diminution de la distribution du flux sanguin et des perturbations du métabolisme normal du disque intervertébral responsable d'une dégénérescence discale plus rapide et rendant le disque intervertébral plus vulnérable. D'autre part, l'exposition aux vibrations corps entier est susceptible d'entraîner une fatigue des muscles lombaires (21). Le taux élevé de lombalgie dans le secteur industriel rejoint celui retrouvé dans la littérature où la plupart des auteurs s'accordent sur le fait que les travaux pénibles sont générateurs de lombalgie accidentelle (6).…”
Section: Discussionunclassified